2020
DOI: 10.18046/j.estger.2020.155.3588
|View full text |Cite
|
Sign up to set email alerts
|

Financial ratios as a powerful instrument to predict insolvency; a study using boosting algorithms in Colombian firms

Abstract: This study is motivated by the importance of accurately predicting insolvency before it happens. The paper aims to develop an insolvency prediction model for Colombian firms with one, two and three years of anticipation through financial ratios, keeping sample structures and taking into account insolvency-related regulation. This research contributes to the literature because unlike many studies, it takes legislation into account, explains the different types of financial ratios, and uses boosting algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Due to financial debts are less expensive than equity, especially for the interest tax shields. On the other hand, it has been demonstrated that high debt increases the likelihood of insolvency [14]. The comparison of the accuracy of various prediction models and the decision which model has SHS Web of Conferences 9 2, 0 (2021) Globalization and its Socio-Economic Consequences 2020 [16].…”
Section: Financial-economics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to financial debts are less expensive than equity, especially for the interest tax shields. On the other hand, it has been demonstrated that high debt increases the likelihood of insolvency [14]. The comparison of the accuracy of various prediction models and the decision which model has SHS Web of Conferences 9 2, 0 (2021) Globalization and its Socio-Economic Consequences 2020 [16].…”
Section: Financial-economics Analysismentioning
confidence: 99%
“…(1 -short-term receivables) (5); Adjusted current assets = financial accounts + adjusted inventory + adjusted short-term receivables (6); Adjusted short-term liabilities = short-term liabilities. (1 -short-term commitments) (7); Available liquidity = financial accounts / short-term external capital (8); Current liquidity = (financial accounts + short-term receivables) / short-term external resources (9); Total liquidity = (inventories + financial accounts + short-term receivables) / short-term external capital (10); Operating liquidity = financial accounts / short-term liabilities (11); Current operating liquidity = (financial accounts + short-term receivables) / short-term liabilities (12); Total operating liquidity = (stocks + financial accounts + shortterm receivables) / short-term liabilities (13); Adjusted available liquidity = financial accounts / adjusted short-term liabilities (14); Adjusted current liquidity = (financial accounts + adjusted balance of receivables) / adjusted balance of short-term liabilities (15); Adjusted total liquidity = adjusted balance of current assets / adjusted balance of current liabilities (16). 3 Results…”
Section: Ex Post Financial Analysismentioning
confidence: 99%
“…Looking at previous research contributions, we find that financial analysis as an input to forecast was employed partially, as a large group of researchers used financial analysis to predict the future financial conditions of companies, and we mention from that: the study (Jiang & Lee, 2012), which confirmed the possibility of using financial ratios to predict basic returns For stocks, and a study (Yang & Dimitrov, 2017) that found that using processed data is useful in predicting companies' default. Indeed, some studies have determined the accuracy of using financial analysis in forecasting, such as the study (Correa-Mejía & Lopera-Castaño, 2020), which concluded that the financial ratio analysis could be used to predict the failure of companies for a period of three years with an accuracy rate of 70%, this percentage increased to 80% According to the results of the study (Alireza & others, 2021).also, (Slimi, 2012) studied the effect of business cycles in certain countries in the Middle East and North Africa on the profitability of banks. The study concluded that the effect of recession is not certain on the profitability of banks and it varies by country and a study of (Ibrahim, et al, 2017) discussed several macro and partial indicators including financial indicators for banks-that can be used as an early system to monitor financial crises before they occur.…”
Section: Previous Studiesmentioning
confidence: 99%
“…That way, based on information obtained from a set of financial reports, the management would be able to recognize early signals of business failure. Forecasting the business failure of companies, according to previous research, can be done using a traditional model (based on selected indicators) [15][16][17], but also by using existing, modern models (Altman Z"model, Springate model, Zmijewski model, Kralicek's model, BEX model, logit model) [18][19][20][21][22] to recognize early signals of business failure, i.e. determine whether the analyzed company will go bankrupt or not.…”
Section: Introductionmentioning
confidence: 99%